2014
DOI: 10.1371/journal.pone.0089115
|View full text |Cite
|
Sign up to set email alerts
|

Differential Function of Themis CABIT Domains during T Cell Development

Abstract: Themis (also named Gasp) is a newly identified Grb2-binding protein that is essential for thymocyte positive selection. Despite the possible involvement of Themis in TCR-mediated signal transduction, its function remains unresolved and controversial. Themis contains two functionally uncharacterized regions called CABIT (cysteine-containing, all-β in Themis) domains, a nuclear localization signal (NLS), and a proline-rich sequence (PRS). To elucidate the role of these motifs in Themis’s function in vivo, we est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…GRB2 contains a central Src homology 2 (SH2) domain flanked by two SH3 domains [7]. The THEMIS:GRB2 interaction was shown to require the THEMIS PRS which binds to one of the GRB2 SH3 domains [810]. GRB2, via its SH2 domain, recruits THEMIS to the scaffolding transmembrane T cell adapter Linker for Activation of T cells (LAT) upon TCR engagement [8, 9, 11].…”
Section: The Fog Begins To Clearmentioning
confidence: 99%
See 3 more Smart Citations
“…GRB2 contains a central Src homology 2 (SH2) domain flanked by two SH3 domains [7]. The THEMIS:GRB2 interaction was shown to require the THEMIS PRS which binds to one of the GRB2 SH3 domains [810]. GRB2, via its SH2 domain, recruits THEMIS to the scaffolding transmembrane T cell adapter Linker for Activation of T cells (LAT) upon TCR engagement [8, 9, 11].…”
Section: The Fog Begins To Clearmentioning
confidence: 99%
“…GRB2, via its SH2 domain, recruits THEMIS to the scaffolding transmembrane T cell adapter Linker for Activation of T cells (LAT) upon TCR engagement [8, 9, 11]. The THEMIS:GRB2 interaction is required for THEMIS in vivo activity [9, 10, 12] indicating that recruitment of THEMIS to LAT by GRB2 is essential for its function.…”
Section: The Fog Begins To Clearmentioning
confidence: 99%
See 2 more Smart Citations
“…Though the CABIT structural motifs have been identified by sequence conservation, their structure-function relationships have yet to be clearly defined. Recent studies have shown that deletion of a part of the CABIT-1 domain (⌬150-174) in mouse THEMIS causes a defect in T cell development (45). We show that the I23N mutation in the CABIT-1 domain causes protein instability in primary thymic cells and in transfected cells, suggesting that I23N may cause misfolding of the protein, which is consequently targeted for degradation.…”
Section: Discussionmentioning
confidence: 69%